2013
DOI: 10.1080/17429145.2012.716455
|View full text |Cite
|
Sign up to set email alerts
|

Polyamines: potent modulators of plant responses to stress

Abstract: Polyamines (PAs) are aliphatic polycations that are widespread in living organisms. In this review, we are focusing the correlation between endogenous PA titers and physiological perturbations and on the protective role of various analogues of PAs against abiotic stresses. PAs are involved in many physiological processes, such as cell growth and development and also respond to diverse abiotic stresses. Polyamines level shifts in different ways depending on several factors, such as plant species, tolerance or s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
49
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(53 citation statements)
references
References 135 publications
(143 reference statements)
2
49
0
2
Order By: Relevance
“…Several reviews [6,[9][10] have dealt with the relationship between tolerance and the capacity to enhance the synthesis of polyamines upon exposure to stress. Plants overexpressing genes encoding enzymes involved in polyamine biosynthesis accumulate higher levels of polyamines and show enhanced tolerance to various stresses [9][10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several reviews [6,[9][10] have dealt with the relationship between tolerance and the capacity to enhance the synthesis of polyamines upon exposure to stress. Plants overexpressing genes encoding enzymes involved in polyamine biosynthesis accumulate higher levels of polyamines and show enhanced tolerance to various stresses [9][10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…Plants overexpressing genes encoding enzymes involved in polyamine biosynthesis accumulate higher levels of polyamines and show enhanced tolerance to various stresses [9][10][11][12][13][14]. This suggests that an increase in polyamine synthesis is effective against all types of stress.…”
Section: Introductionmentioning
confidence: 99%
“…Now, in response to oxidative stress, a number of elicitor moieties have been recognized for their efficacy to moderate the generated ROS. Among the elicitors, polyamine is one of the integral component that involved in alleviation of various abiotic stresses like salinity, drought, chilling, oxidative stress, metal toxicity, and paraquat (Fariduddin et al 2013). This study also showed that putrescine (Put), a di-amine, which is a straight chain aliphatic compound (Farooq et al 2009), diversed the cellular responses like osmotic adjustment, membrane functioning, modulation of metabolic pathways, and gene activation for detoxifications of ROS as reported in plant system (Ding et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…ODC carries out the reaction of ornithine decarboxylation directly to Put (Fariduddin et al, 2013). The biosynthesis of Put is also preceded by reactions of Arg decarboxylation by ADC to Agm (Lightfoot and Hall, 2014).…”
Section: Figure 8 Suggested Biogenic Amines Biosynthesis In Plantsmentioning
confidence: 99%